Flavanon - Novi Fatmawati; Novi Anggreini; Ratih Dewi Saputri; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung (JURNAL KIMIA MULAWARMAN, 2018)
Two isoprenylated flavanones namely as lonchocarpol A (1) dan lupinifolin (2) were isolated from the stem bark of Limonia accidissima L. Erythrina fusca L. Their structures were determined based on spectroscopic data such as UV, IR, MS and NMR. Compounds 1–2 were evaluated for their antimalarial against Plasmodium falciparum strain 3D7 showing their IC50 were 1.18 and 0.8 µg/ml, respectively and very high activity.